Pemanfaatan Teknologi Mikoriza di Tanah Karst Petani Desa Karangasem Kabupaten Gunung Kidul Yogyakarta - Yuslinawari Yuslinawari; Sri Suryanti; Siwi Istiana Dinarti (Magister of Forestry,Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
The community of Karangasem Village works as farmers. The land condition in Karangasem village dry land , high content of lime carbonate and shallow soil solum so that the percentage of plant life is low. To overcome these problems, it is necessary to increase knowledge of land management that is suitable for karst areas. Prior to the application of new technology, it is necessary to measure the level of knowledge of farmers towards technology and changes in attitudes that occur after understanding the technology. These factors encourage Community Service (PkM) with assistance to farmers which aims to foster farmer changes that include the level of knowledge, skills, abilities, attitudes, and motivation for farming activities carried out. The PkM method is done by focus group discussions , counseling, training and assistance for mycorrhizal applications on woody plants, icons of rare tree conservation and land management. The implication of the activity is that 92% of farmers who do not know about mycorrhizal inoculation technology and its benefits for soil and plants become 100% aware and know the benefits of mycorrhizal application.. Changes in farmers' attitudes have implications for the pattern from chemical agricultural changes to organic farming and environmentally friendly agriculture.